Technology and Society - Kleinman, Daniel (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this course, students are introduced to a wide range of work on technology, the social forces shaping its development and the social impacts of its adoption. I seek to encourage students to examine their assumptions about technology and its relationship to society. At the same time, I have no desire for students to accept the arguments made by me or in course materials as a new faith. Instead, I will attempts to promote a classroom environment in which the materials we read can be closely examined–where arguments can be challenged and evidence assessed.